Synthesis and anti-inflammatory activity evaluation of novel triazolyl-isatin hybrids. (1st November 2016) - Sharma, Pramod K.; Balwani, Sakshi; Mathur, Divya; Malhotra, Shashwat; Singh, Brajendra K.; Prasad, Ashok K.; Len, Christophe; Van der Eycken, Erik V.; Ghosh, Balaram; Richards, Nigel G. J.; Parmar, Virinder S.
Abstract: New isatin-triazole based hybrids have been synthesized and evaluated for their inhibitory activity of TNF-α induced expression of Intercellular Adhesion Molecule-1 (ICAM-1) on the surface of human endothelial cells. Structure-activity relationship (SAR) studies revealed that the presence of the electron-attracting bromo substituent at position-5 of the isatin moiety played an important role in enhancing the anti-inflammatory potential of the synthesized compounds. Z-1-[3-(1 H -1, 2, 4-Triazol-1-yl)propyl]-5-bromo-3-[2-(4-methoxyphenyl)hydrazono]indolin-2-one (19 ) with an IC50 = 20 μM and 89% ICAM-1 inhibition with MTD at 200 μM was found to be the most potent of all the synthesized derivatives. Introduction of 1, 2, 4-triazole ring and electron-donating methoxy group on the phenylhydrazone moiety resulted in four-fold increase of the anti-inflammatory activity.